Consumption Reduction Solution of TV News Broadcast System Based on Wireless Communication Network - Haifeng Qiang (Complexity)
At present, the news broadcast system using mobile network on the market provides the basic functions required by TV stations, but there are still many problems and shortcomings. In view of the main problems existing in the current system and combined with the actual needs of current users, this paper has preliminarily developed a news broadcast system based on 5G Live. The card frame adaptive strategy significantly improves the user experience by using gradual video frame buffering technology. Hardware codec technology significantly reduces the consumption of system resources; H.264 high-compression algorithm can reduce network bandwidth by 50% compared with MPEG-2 and MPEG-4 without a significant change in image quality. At the same time, the use of mobile video acquisition terminals in the system not only solves the problem that satellite broadcast vehicles cannot reach the site due to the lack of roads but also greatly reduces the cost of early deployment and late maintenance of the news broadcast system. This paper studies the card frame adaptive strategy, the system resource consumption reduction solution, and the deployment scheme of the mobile video and audio transmission terminal, which is of great significance to improve the design and research of the news broadcast system under the wireless network application and also has certain reference value for the design of other broadcasting and television solutions.